KCC Paint Sdn Bhd / Muammar Muzammir Zubir - Zubir, Muammar Muzammir (Faculty Of Chemical Engineering, 2021)
As overall throughout this industrial training, I realized that teamwork and communication is really important. With good communication and teamwork, workflow will become smooth and clear. This help to speed up the work in QC. Other than that, the discipline also important in KCC. Employees are not allowed to use phone while working. And KCC always prioritize the safety, KCC provide safety shoes for every employee and every week will have a safety talk by safety officer. Real working environment are really different with environment in college. In workplace, the environment is really challenging especially in mental and physical. From my internship experience in KCC Paint, I gained new experience, useful knowledge and new skill. This is really help me to improve for my working life in the future. I also get an insight in facing working life and be ready for the next step in my career. In relating to chemical engineering, I learnt how use the equipment to determine viscosity, specific gravity and pH. In college, I learnt the theories how to calculate the viscosity and specific gravity. I'm glad to have a chance to use the equipment. During the internship, I also saw the process to treat water. This is important to avoid water pollution. I also used my safety knowledge to avoid any unwanted incidents. Thus, I realized that all the knowledge I learnt at college really help me in working. Lastly, I noticed some things that should be improve. First is increase the manpower in QC and packing. This is because manpower for both QC (water-based paint and solvent based paint) is 2 people per QC. When one of the worker absent, it will inconvenience the other worker especially when the order is too many. And the process to pass the product become slower. It same goes to the packing department. In packing department, they need to packing product such as 3000L in 500ml cans. So, by increasing the manpower, the packing process can become faster and easier to all the packing worker